Moderate-to-Vigorous-Intensity Physical Activity Observed in People With Diabetes-Related Foot Ulcers Over a One-Week Period. (September 2019) - Lee, Maggie; van Netten, Jaap J.; Sheahan, Helen; Lazzarini, Peter A.
Background: Regular moderate-to-vigorous-intensity physical activity results in health benefits in people with diabetes. No study has observed the moderate-to-vigorous-intensity physical activity typically performed by people with diabetes-related foot ulcers (DFU) in their everyday free-living environments. We observed the bouts, and accumulated time, spent doing moderate-to-vigorous-intensity physical activity in cases with DFU compared with diabetes-related peripheral neuropathy (DPN) and diabetes (DM) controls over a one-week period. Methods: This was a secondary analysis of a cross-sectional case-control study. Participants wore a multisensor device for >5 days (>22 hours per day). Primary outcomes included the number, duration (minutes) and intensity (metabolic equivalent tasks [METs]) of bouts of moderate-to-vigorous-intensity physical activity (defined as at least >3 METs for >10 consecutive minutes). Secondary outcomes included the total accumulated times spent doing moderate-to-vigorous-intensity physical activity (>3 METs) and doing sedentary-intensity activity (<1.5 METs). DFU subgroups with minor amputations and nonremovable offloading devices were also analyzed. Results: Overall, 15 DM, 23 DPN, and 27 DFU participants were included. All groups recorded similar low median daily numbers (0.33, 0.29, 0.25 numbers, respectively), duration (15, 17, 14 minutes), and intensity of daily bouts of moderate-to-vigorous-intensity physical activity (4.1, 4.3, 3.9 METs) (all, P > .1). Median accumulated daily time spent doing moderate-to-vigorous-intensity physical activity was also similar (40, 37, 36 minutes; P > .8). Those with DFU had more mean accumulated daily time spent doing sedentary-intensity activity (796 minutes) compared to DPN (720 minutes; P < .05), but not compared to DM (728 minutes; P < .08). DFU subgroups with minor amputations had more median accumulated daily time spent doing moderate-to-vigorous-intensity physical activity (66, 28 minutes; P < .05) and less mean time doing sedentary-intensity activity (745, 837; P < .05) than those without amputations. Conclusions: People with DFU performed similar low numbers of daily bouts of moderate-to-vigorous-intensity physical activity to controls, but spend more time doing sedentary-intensity activities. Interventions that gradually increase the moderate-to-vigorous-intensity physical activity in people with DFU should be investigated.